Teaching, learning, and growing: the construction of a novice L2 writing teacher’s personal practical knowledge - Mingyu Li (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract Although research interest in second language (L2) teachers has grown, novice L2 teachers remain understudied, especially writing teachers. Existing research on L2 writing teachers has largely centred on cognitive development, often overlooking crucial personal and socio-contextual aspects. Utilising a narrative case study approach, this study addresses the gap by exploring the personal practical knowledge of a novice L2 writing teacher, offering a personal, socio-contextual perspective on teacher knowledge. The study utilises narrative interviews, reflective journal entries and teaching artefacts to construct a comprehensive portrayal of the teacher’s journey of professional development. Findings reveal that novice teachers’ self-image, a significant component of their personal practical knowledge, is profoundly influenced by their past experiences and continually guides their teaching. The study calls for a re-evaluation of training programmes to incorporate strategies that help novice teachers integrate their personal histories and contextual realities into their professional practice. Recommendations for future research include cross-cultural and cross-disciplinary longitudinal studies that incorporate multimodal narratives to more effectively track the evolution of novice teachers’ practical knowledge and its impact on teaching efficacy in the global educational landscape.